2020
DOI: 10.1021/acsapm.0c01006
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Copolymers Derived from Butanosolv Lignin and Acrylamide: Synthesis, Properties in Water Solution, and Potential Applications

Abstract: In this work, a series of amphiphilic lignin-acrylamide copolymers was synthetized via a "grafting from" approach using α-butoxylated organosolv lignin. This lignin is obtained in high yield via a mild organosolv extraction with butanol and contains a well-defined modified β-O-4 structure that allows for site-selective modification of the primary alcohol in the γ-position. The modified lignin was then used as a precursor of amphiphilic copolymers by reaction with acrylamide, either via free radical polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…As previously shown, GA‐lignin (Figure 3a and Figure 6, red bars, and Table S5) was able to lower the surface tension of the water/air from 72.8 (Figure 6, green bar) to 31 mN m −1 regardless of the pH of the aqueous phase. Specifically, GA‐lignin at pH 7 and 14 lowered the surface tension as well as or more than all the other lignins, such as the industrial Kraft lignin and lignosulfonates, or literature‐reported lignins that underwent further chemical modification to impart them with surfactant properties including sulfomethylated lignin, [39] dodecyl succinic acid‐, [35] polyethylene glycol (PEG)‐, [23] or polyacrylamide (PAM)‐ [40] grafted lignins (Figure 6, blue bars).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously shown, GA‐lignin (Figure 3a and Figure 6, red bars, and Table S5) was able to lower the surface tension of the water/air from 72.8 (Figure 6, green bar) to 31 mN m −1 regardless of the pH of the aqueous phase. Specifically, GA‐lignin at pH 7 and 14 lowered the surface tension as well as or more than all the other lignins, such as the industrial Kraft lignin and lignosulfonates, or literature‐reported lignins that underwent further chemical modification to impart them with surfactant properties including sulfomethylated lignin, [39] dodecyl succinic acid‐, [35] polyethylene glycol (PEG)‐, [23] or polyacrylamide (PAM)‐ [40] grafted lignins (Figure 6, blue bars).…”
Section: Resultsmentioning
confidence: 99%
“…[35]; PAM-grafted butanosolv lignin: Ref. [40]; PEG-grafted enzymatic lignin: Ref. [23]; sulfomethylated alkali lignin: Ref.…”
Section: Surface Tension Comparison Of Ga-lignin With Other Lignin-ba...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line, RDRP methods have been recently applied also to the synthesis of well-defined (meth)acrylic polymers from lignin fractions of lignocellulosic materials. [142][143][144] Future opportunities we envision in this area include the synthesis of more complex polymeric architectures, scale up of both monomer syntheses and polymerizations, as well as bio-based poly(meth)acrylate designed for currently unexplored applications. Block copolymers give interesting opportunities due to their ability to phase separate and form selfassembled nanostructures, which could be exploited further.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonate lignin is the most important anionic structure in lignin, and its main sources include sulfite pulping waste liquor and sulfonated alkali lignin. Chemically modified amphiphilic lignin polymers are typically used as fine chemicals and are used for practical applications such as suspension, solubilization, wetting, and as detergent agents. Most existing amphiphilic materials such as surfactants are toxic, nonbiodegradable, and pollute the environment. In the future, surfactant products will gradually develop in the direction of green raw materials, environmentally friendly products, and safe treatment.…”
Section: Introductionmentioning
confidence: 99%